Pedagogical evaluation in the courses of Permanent Education Center of Greater São Paulo: fragilities and challenges - Nico Monteiro, Paulo Henrique; Barboza, Renato; Rivero Pupo, Lígia; Barros Calife Batista, Karina; Loureiro Escuder, Maria Mercedes (O Mundo da Saúde, 2007)
Workers training of the health sector is one of the great challenges for the consolidation of Brazil’s Unified Health System. Due to this, the Health Ministry instituted in 2004 the National Policy of Permanent Education in Health, structuring and defining technical and political guidelines implemented by Permanent Education Centers. This interinstitutional space congregates education organizations, managers and health professionals. In the present article the pedagogical actions approved and financed by the Permanent Education Center of Greater São Paulo in the period 2004-2005 were characterized aiming to investigate the proposals for pedagogical evaluation presented by the involved institutions. The actions were categorized regarding the type of executor institution, education modality, target public, type of evaluation adopted (diagnostic, summative, formative), the focus of the evaluation process (pupils, teachers, content, methodology), the specification of evaluation criteria and their relation with the actions’ general objective. Data analysis points out that the pedagogical evaluation process of the courses offered by the Center presented fragilities in the phases of proposal, planning and execution. We therefore recommend that pedagogical evaluation subjects be discussed inside the Centers in order to characterize the permanent education processes directed to Brazil’s Unified Health System professionals.